A review of WTO disputes on TRIPS: Implications for use of flexibilities for public health - Nirmalya Syam (South Centre, 2022)
The use of TRIPS flexibilities by WTO members involves interpretation of the obligations under TRIPS which can be challenged under the WTO dispute settlement system. Mutually agreed solutions, panel or Appellate Body decisions adopted in such disputes can thus impact the scope of TRIPS flexibilities to address, among others, public health objectives. This paper explores how the WTO dispute settlement system applies to disputes under TRIPS, and reviews the outcomes of the disputes relating to the implementation of TRIPS obligations in the context of pharmaceutical products. The paper points to both systemic and substantive concerns arising from the application of the dispute settlement system to disputes under TRIPS. It finds that the dispute settlement system is not aligned to the unique nature of the TRIPS Agreement in the WTO as an agreement that creates positive obligations, and consequently how jurisprudence arising under disputes concerning other covered agreements having negative obligations, have led panels and Appellate Bodies to adopt narrow interpretations of the scope of TRIPS flexibilities in some of the few disputes arising under the TRIPS Agreement. Moreover, mutually agreed settlements adopted in the context of some of the disputes arising under TRIPS have also led to the adoption of TRIPS plus standards, limiting the scope of TRIPS flexibilities. However, in a recent decision, the WTO panel has also relied on the Doha Declaration on TRIPS and Public Health as a subsequent agreement to guide the interpretation of its provisions. In this context, the paper advances some suggestions to address the systemic and substantive issues arising from the application of the dispute settlement system to the TRIPS Agreement.
Keywords: 300; Internationale Schiedsgerichtsbarkeit; TRIPS; Immaterialgüterrechte; Arzneimittel; Welt